'Aid in a Pressure Cooker': Humanitarian Action in the Occupied Palestinian Territory - Fast, Larissa (Tufts Archival Research Center, 2008)
Paper dated november, 2006. The Humanitarian Agenda 2015 study (Donini et al. 2006) has examined the effects of four major challengesuniversality, terrorism, coherence, and securityto humanitarian action in context-specific situations. This study of the occupied Palestinian territory (oPt) is part of Phase II of HA2015 which includes a larger set of case studies. As with the other case studies, the present report offers insights into the way in which these four major variablesor petalsare interrelated and impact on humanitarian action.